Telling Fairy Tales in the Boardroom How to Make Sure Your Organization Lives Happily Ever After - Kets de Vries, Manfred F.R (INSEAD Business Press, 2016)
We know where we are with a fairy story. There is a cast of predictable characters, the hero or heroine is submitted to terrible trials, cruelty, and injustice but in the end the baddies get their comeuppance, good triumphs, and everyone lives happily ever after. In this book Manfred Kets de Vries, one of the world's leading authorities on the psychology of leadership, and a pioneering practitioner in the field of psychodynamic executive coaching, draws on the format of traditional fairy tales and tells us five stories that dramatize five key themes of dysfunctional leadership. The accompanying commentaries analyze each tale and examine the ways in which it applies to leadership behavior and organizational practices. This diagnostic element is supported by self-assessment tests that reinforce the main lessons of each tale and guide the reader's interpretation of the results. With Kets de Vries's guidance you'll be able to help your clients create best places to work, where everyone is the best they can be, and lives 'happily ever after'.